Relation between calcium levels and adenosine deaminase activity in serum in pre- and postpartum of dairy cow. (November 2016) - Fritzen, Alexandro; Albani, Kassio; Machado, Gustavo; Bottari, Nathieli; Alves, Mariana; Schetinger, Maria; Morsch, Vera; Giuriatti, Jessica; Silva, Aleksandro
Abstract The transition period is marked by intense metabolic changes that defy calcium homeostasis, and compromise the immune capacity of dairy cows, what denotes interaction between metabolic status and immune activity. The adenosine deaminase (ADA) regulates adenosine levels; a molecule with anti-inflammatory properties that can act in reducing the production of pro-inflammatory cytokines and reactive oxygen species (ROS), which in exacerbated production is harmful to health. Therefore, the aim of this study was to evaluate the relationship between seric levels of calcium levels and ADA in prepartum and postpartum of dairy cows. To evaluate these variables, Holstein cows were subjected to blood collection in the transition period (days 20, 10, and 5 prepartum; and days 3, 7, 12, and 20 postpartum) and where we evaluated the serum levels of calcium and the ADA activity. An increase in the ADA activity was observed mean day 20 to day 10 postpartum (P < 0.001). Numerically, in other periods evaluated, ADA activity was higher when compared to day 20 prepartum. The serum calcium significantly reduced from 5 days prepartum, keeping smaller the day 20 prepartum until day 12 postpartum (P < 0.02). There was a negative correlation between serum calcium levels and ADA activity. The increase of ADA can be related to modulation of the inflammatory response that occurs during the transition period for cows.